2013
DOI: 10.1163/15685373-12342105
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Quality and Persuasiveness: Germans Are Not Sensitive to the Quality of Statistical Evidence

Abstract: For a long time, research in communication and argumentation has investigated which kinds of evidence are most effective in changing people's beliefs in descriptive claims. For each type of evidence, such as statistical or expert evidence, high-quality and low-quality variants exist, depending on the extent to which evidence respects norms for strong argumentation. Studies have shown that participants are sensitive to such quality variations in some, but not in all, cultures. This paper expands such work by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 27 publications
3
14
0
5
Order By: Relevance
“…As another example, Hornikx and Hoeken (2007) found that a claim was perceived as more persuasive by their participants when it was supported by high-quality data (e.g., statistical evidence), although this effect was observed only in Dutch but not French students. In another study (Hornikx & ter Haar, 2013), the same effect was observed in Dutch but not German students.…”
Section: Lay Readers' Evaluations Of Informal Argumentssupporting
confidence: 54%
See 2 more Smart Citations
“…As another example, Hornikx and Hoeken (2007) found that a claim was perceived as more persuasive by their participants when it was supported by high-quality data (e.g., statistical evidence), although this effect was observed only in Dutch but not French students. In another study (Hornikx & ter Haar, 2013), the same effect was observed in Dutch but not German students.…”
Section: Lay Readers' Evaluations Of Informal Argumentssupporting
confidence: 54%
“…As another example, Hornikx and Hoeken (2007) found that a claim was perceived as more persuasive by their participants when it was supported by high-quality data (e.g., statistical evidence), although this effect was observed only in Dutch but not French students. In another study (Hornikx & ter Haar, 2013), the same effect was observed in Dutch but not German students.Although lay readers engage in argument evaluations to some extent, various studies show that they are not always accurate in their evaluations. For example, van Eemeren, Garssen, and Meuffels (2012) found that ad hominem attacks were rejected by students as unreasonable, but were perceived as more reasonable when they were presented as if they were critical questions regarding authority argumentation.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…So, procedural norms, being based on social conventions, may be expected to vary across cultures.1 In contrast, epistemic norms, being based on, presumably universal, mathematical laws, may be expected not to vary between cultures. However, research looking at the effects of levels of evidence quality on argumentation, presumably underpinned by epistemic norms, has revealed differences (e.g., Hornikx & Hoeken, 2007;Hornikx & ter Haar, 2013).…”
Section: Journal Of Cognition Andmentioning
confidence: 99%
“…The decisive role of social interactions in brainbuilding is theoretically and experimentally substantiated, and the specifics of argumentation in the situations of collective problem solving are investigated (Inglis & Mejia-Ramos, 2009;Ravenscroft & McAlister, 2008;Rapanta, 2018). The argument is considered as a social and cultural resource (Rigotti & Morasso, 2010;Erduran & Jimenez-Aleixandre, 2008;Karaslaan, Hohenberger, Demir, Hall & Oaksford, 2018;Hornikx & Hoeken, 2007;Hornikx & ter Haar, 2013), as a means of activating the educational process in the system of secondary and higher education (Albano & Dello, 2019;Ragonis & Shilo, 2018;Schwarz & Baker, 2016;Albe 2008;Simon, Erduran & Osborne, 2006).…”
Section: Introductionmentioning
confidence: 99%